Farmers' Perspective on Converting Their Paddy Fields in West Java Province - Asmadi Adnan; Septina Marryanti Prihatin (Agriekonomika, 2023)
The conversion of paddy fields continues to increase rapidly, potentially affecting rice production and threatening national food/rice security. This paper presents farmers' perspectives on various indicators of drivers, controllers and decision-making influencing land conversion. The study is based on a policy and literature approach, supported by field studies using qualitative-quantitative mixed methods in West Java Province. The results show that the driving indicators of land conversion are near main roads/highways; near settlements/trade/industry/ services; and densely populated. Indicators of restraining conversion are space utilization in line with the Spatial Plan; provision of incentives for means of production; and the imposition of land tax disincentives. The most decisive indicators of conversion decision making for farmers' choices are the control / ownership of narrow rice fields; and the production value of rice fields is low.